2020
DOI: 10.46281/ijafr.v5i1.489
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review on the Association between Earnings Management and Corporate Social Responsibility

Abstract: This paper aims to give an overview of the existing literature on the Earnings Management (EM) and Corporate Social Responsibility (CSR) relationship in different countries. This paper reviews preceding studies concerned about EM, CSR and their relationship. Out of 23 works of literature, 11 studies found a negative relationship, 6 studies found a positive relationship, 2 studies found blended relationships in case of different situations and 4 studies found no connection between CSR and EM. Most of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
1
8
1
Order By: Relevance
“…Thus, our results show the publication of articles in this field by a large number of authors in more than 50 countries around the world. However, our analysis of geographical dispersion coincides with the previous study by Parvin et al (2020), as it indicates that the most prolific current research is concentrated in a number of countries, such as China and the US, followed by the UK and Spain. In addition, this bibliometric review differs from others published to date, analyzing the productivity of organizations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, our results show the publication of articles in this field by a large number of authors in more than 50 countries around the world. However, our analysis of geographical dispersion coincides with the previous study by Parvin et al (2020), as it indicates that the most prolific current research is concentrated in a number of countries, such as China and the US, followed by the UK and Spain. In addition, this bibliometric review differs from others published to date, analyzing the productivity of organizations.…”
Section: Discussionsupporting
confidence: 89%
“…However, our study differs from previous studies by Velte (2020) and Parvin et al (2020), indicating that, in 2015, there was a growing interest in the study of CSR's influence on EM. It has thus been confirmed that there has been a recent and successful period of related academic literature, specifically from 2015 to date.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The legitimacy theory, on the other hand, argues that firms disguise their opportunistic behaviour through disclosing information voluntarily (Li et al, 2012;Parvin et al, 2020). Li, Mangena, & Pike (2012) argued that managers might voluntarily reveal information to shade their opportunistic behaviour and to protect themselves against any possible reaction from stockholders.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The external audit, as a mechanism for controlling management activity, has been the subject of numerous research studies, including that of Chen, Hope, Li, & Wang (2011), who believe that the intervention of external auditors helps to mitigate the opportunistic behaviour of managers and therefore constitutes a guarantee of the quality of financial information. Probably management activities are increased when asymmetric information is more important (Parvin, Rana & Shams, 2020) so an external audit quality may limit this behaviour. Also, García, Martínez, & Sánchez (2014) state that audit quality generally helps to restrict the practice of results management.…”
Section: Introductionmentioning
confidence: 99%